Design, development and validation of a mobile application for goal setting and self-monitoring of dietary behaviors - Quesada López, Christian Ulises (2016)
The potential of mobile technologies are being used increasingly has not been fully exploited in relation to health research. There are Application (app) stores have thousands of healthrelated apps in the market, but generally, what is available publicly has not been fully evaluated by experts. This paper presents a case study where Human-Computer Interaction techniques and agile methodologies were applied in the design, development and validation of a health system in an interdisciplinary project. The system consisted of a mobile software platform that includes a nutrition mobile application for dietary self-monitoring based on behavioral change techniques. The essential background on behavioral change is provided. The application was designed using contextual design and other DCU methodologies. The system architecture and the main features of the end user mobile application are shown. The prototype was evaluated by nutrition domain experts and the preliminary results suggest that the application can improve the nutrition care process by facilitating a more effective communication between nutritionists and patients.